2011
DOI: 10.1111/j.1601-0825.2011.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent orofacial muscle pain

Abstract: The pathophysiology of persistent orofacial myalgia has been the centre of much controversy. In this article we suggest a novel descriptive term; Ôpersistent orofacial muscle pain' (POMP) and review current evidence that supports the hypothesis that the induction of POMP involves the interplay between a peripheral nociceptive source in muscle, a faulty central nervous system component and decreased coping ability. In this context it is widely accepted that a complex interaction of variable intrinsic and extrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 205 publications
(265 reference statements)
3
51
0
1
Order By: Relevance
“…Looking at this from another perspective, the term ‘persistent’ relates to the clinical observation that local surgical treatments to the dento-alveolar tissues is ineffective at relieving the pain symptom of this disorder, which is useful perception to promulgate at the present time given the failure of contemporary approaches to treatment. Furthermore, the term ‘persistent’ is the term recently proposed to describe a similar pain-related phenomenon presenting within the muscles of mastication (18) and is therefore a consistent terminology that can be used to expand this taxonomy. Finally, because pain in ontological terms is a symptom, this entity would better be described as a pain disorder , a specific disease entity.…”
Section: Resultsmentioning
confidence: 99%
“…Looking at this from another perspective, the term ‘persistent’ relates to the clinical observation that local surgical treatments to the dento-alveolar tissues is ineffective at relieving the pain symptom of this disorder, which is useful perception to promulgate at the present time given the failure of contemporary approaches to treatment. Furthermore, the term ‘persistent’ is the term recently proposed to describe a similar pain-related phenomenon presenting within the muscles of mastication (18) and is therefore a consistent terminology that can be used to expand this taxonomy. Finally, because pain in ontological terms is a symptom, this entity would better be described as a pain disorder , a specific disease entity.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging evidences suggest that both male and female hormones may contribute to marked gender-related differences in the occurrence of musculoskeletal pain 13 . Gender differences may be also expressed by pain processing in nociceptive pathways as well as by environmental and cultural issues 11 . Our results confirm previous findings that regions of greater pain reports are located in the upper body areas, both for males and females.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental parameters such as ethnicity, culture, stress and gender are also essential variables 3,11 . With regard to gender, our study has shown a higher prevalence of females seeking OFP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, new terminology was suggested to better describe myogenic masticatory pain, ''Persistent Orofacial Muscle Pain'' (POMP) [16]. According to Benoliel et al, POMP involves the interaction between a peripheral nociceptive source in muscle, an altered central nervous system component and diminished coping ability by the patient.…”
Section: Musculoskeletal Orofacial Painmentioning
confidence: 99%